Authenticity Principle in Conservation of De Javasche Bank of Surabaya: Materials, Substance and Form. (2015) - Kwanda, Timoticin
Abstract: This paper aims to discuss the application of the notion of authenticity principle in the conservation work of De Javasche Bank building in Surabaya in term of form, materials and substance. This heritage building was built in 1910, and it has been unoccupied and dilapidated for decades, subsequently in 2010, the owner, Bank Indonesia began the conservation wok of the building. Data regarding form, materials and substance of the building were collected from field observation during the conservation work from 2011 to 2012, and collected from the Conservation Plan prepared in 2009. Based on the data, the principle of tangible authenticity is tested based upon scientific method to test material authenticity, and through a good knowledge of the typology of objects such as form of the building and elements of the building, materials and substance of the roof and floor tiles, plasters and paints, and the ornaments. The results show that to achieve the principle of authenticity in the conservation work, action taken should follow the ascending degrees of intervention dealing with preservation of the existing state and the original form, material and substance; consolidation of the fabric; restoration of the original building form; rehabilitation of all decay building elements; reproduction of the broken materials with replica such as floor tiles; reconstruction the missing section such as the original name of De Javasche Bank, and adaptation, as new elements such as new lighting systems, air condition, sound system were added to meet the adaptive reuse of the building as multi-purpose hall. In addition, to achieve the principle of authenticity in the conservation work, action taken should follow the principles namely the principle of minimum intervention preserving the original form, material and substance; recognizable as a new when introduce new materials and techniques; and the principle of reversible when in the future if all of the new elements will be detached they will not displace the original elements.